Mapping lung cancer disease in Libya using Standardized Morbidity Ratio, BYM Model and Mixture Model, 2006 to 2011: Bayesian Epidemiological Study - Zulkifley Mohamed (Tanjong Malim, 2019)
Mapping lung cancer disease in Libya using Standardized Morbidity Ratio, BYM Model and Mixture Model, 2006 to 2011: Bayesian Epidemiological Study by Zulkifley Mohamed